2017
DOI: 10.1002/2016ja023348
|View full text |Cite
|
Sign up to set email alerts
|

MAVEN observations on a hemispheric asymmetry of precipitating ions toward the Martian upper atmosphere according to the upstream solar wind electric field

Abstract: The Mars Atmosphere and Volatile Evolution (MAVEN) observations show that the global spatial distribution of ions precipitating toward the Martian upper atmosphere has a highly asymmetric pattern relative to the upstream solar wind electric field. MAVEN observations indicate that precipitating planetary heavy ion fluxes measured in the downward solar wind electric field (−E) hemisphere are generally larger than those measured in the upward electric field (+E) hemisphere, as expected from modeling. The −E (+E) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
35
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 19 publications
(42 citation statements)
references
References 50 publications
6
35
1
Order By: Relevance
“…According to Leblanc et al (), the precipitating ion flux is highly dependent on the solar zenith angle, on the position of the most intense crustal magnetic field structures, and on the orientation of the convective electric field. Indeed, Hara, Luhmann, Leblanc, Curry, Seki, et al () showed that the intensity of the precipitating ion flux peaked on the hemisphere toward which the E SW field pointed (the −E SW hemisphere). In order to restrict the range of solar zenith angle covered by our sampling, we therefore chose to show only reconstructed precipitating ion flux obtained close to the MSO equator, between −10° and 15° in latitude, that is, corresponding to time intervals when MAVEN is located between 200 and 350 km in altitude during the inbound part of its orbit.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…According to Leblanc et al (), the precipitating ion flux is highly dependent on the solar zenith angle, on the position of the most intense crustal magnetic field structures, and on the orientation of the convective electric field. Indeed, Hara, Luhmann, Leblanc, Curry, Seki, et al () showed that the intensity of the precipitating ion flux peaked on the hemisphere toward which the E SW field pointed (the −E SW hemisphere). In order to restrict the range of solar zenith angle covered by our sampling, we therefore chose to show only reconstructed precipitating ion flux obtained close to the MSO equator, between −10° and 15° in latitude, that is, corresponding to time intervals when MAVEN is located between 200 and 350 km in altitude during the inbound part of its orbit.…”
Section: Resultsmentioning
confidence: 99%
“…The MSE angle corresponds to the counterclockwise angle between the vector formed by the latitude and the longitude in MSE of MAVEN during its measurements of the precipitating ion flux and the East MSE direction (MSE longitude equal to +180° and latitude equal to 0°). According to Hara, Luhmann, Leblanc, Curry, Seki, et al (), the precipitating ion flux should reach a maximum around a MSE angle of 270° (ax –E). Indeed, planetary picked up ions should precipitate toward the southern hemisphere (−E) because of the acceleration of the electric field of convection toward this hemisphere.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an example, Hara et al (2018) and Hara et al (2017) have shown that large variation of the precipitating flux can be expected in correlation with the solar wind pressure, the orientation of the electric field of convection, and with the presence of crustal magnetic fields. As an example, Hara et al (2018) and Hara et al (2017) have shown that large variation of the precipitating flux can be expected in correlation with the solar wind pressure, the orientation of the electric field of convection, and with the presence of crustal magnetic fields.…”
Section: Resultsmentioning
confidence: 99%
“…Among these channels, sputtering of the Martian atmosphere by precipitating heavy ions has been identified as one of these potential channels (Luhmann & Kozyra, 1991). Hara et al (2017), analyzing the first 1.5 years of MAVEN measurements, showed that this precipitation is organized with respect to the orientation of the solar wind convection electric field and is dependent on the upstream solar wind conditions. Hara et al (2017), analyzing the first 1.5 years of MAVEN measurements, showed that this precipitation is organized with respect to the orientation of the solar wind convection electric field and is dependent on the upstream solar wind conditions.…”
Section: Introductionmentioning
confidence: 99%